Duelo, ansiedad y depresión en familiares de pacientes en una unidad de cuidados paliativos a los dos meses de la pérdida - Romero, Verónica; Cruzado, Juan Antonio (Psicooncología, 2016)
Aim: This study is going to assess the prevalance of prolonged grief diagnoses and it will evaluate the severity of the symptoms of depression, anxiety and complicated grief two months after a loved one is lost. We also intend to study which variables associated with the risk of grief could be more decisive when diagnosing it, its symptoms and the consequent emotional distress.Method: A total of 66 families of patients in the Palliative Care Unit (PCU) at Hospital San Cecilio in Granada have been evaluated. Measurements were taken two months after the death. This investigation has explored the existing emotional distress using the following questionnaires: Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI), Inventory of Complicated Grief (ICG) and Prolongued Grief Disorder (PG-12).Results: The results show that 33.3% and 21.21% of the sufferers had high levels of depression and clinical anxiety two months after the death. The prevalence of prolongued grief diagnoses, according to the PG-12, is 10.6% and 53.03% of the participants showed symptoms of complicated grief according to the ICG. Additionally, statistically significant differences are found in the sufferers with and without a prolongued grief diagnosis and scores in the ICG and BDI-II. The family’s financial situation is linked to the presence of symptoms of anxiety and depression and complicated grief, with the most determining variable being the risk of grief. Finally, the greater the age of the deceased and the longer the time spent in the PCU is linked to fewer symptoms of grief. However, important links have been found between the sufferers who have experienced stressful critical events prior to losing their loved one, with symptoms of depression, anxiety and complicated grief.Conclusions: The high numbers of cases of symptoms of complicated grief and levels of anxiety and clinical depression two months after a death suggests that early interventions should be carried out in those individuals with greater vulnerability.
Keywords: Complicated grief; risk variables; anxiety; depression and grief.